(untitled) (Academicia Globe: Inderscience Research, 2024)
This study explores the impact of cultural heritage (CH) on inbound tourist development (ITDI) in economic, social, and environmental domains, as well as how inhabitants perceive tourism development. This study utilized a quantitative cross-sectional research approach with random sampling. The study found that the TDI components (economic and social) positively improve CH, whereas environmental effect is not a significant predictor. CH has a crucial role in mediating the interaction between ITDI (economic and social effect). This is similar to the negligible direct impact.